A method of manufacturing a filter cartridge, a method of cleaning

CN118416552BActive Publication Date: 2026-10-23NINGBO FOTILE KITCHEN WARE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310050444.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2026-10-23
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

该发明中,矿化滤芯的主要作用是向水中稳定释放矿物质,由于天然矿石成分复杂,在矿化原水的过程中,难免会同时释放出重金属;同时,其碳棒对重金属的去除能力较弱,难以兼顾对重金属的去除

Benefits of technology

[0022]与现有技术相比,本发明的优点在于:采用分层熔喷工艺制备出矿化层位于外层、聚合物层位于内层的双层滤芯,待处理的水由熔喷滤芯外层流入内层,当水流经外层时,矿化层中的矿化填料对其进行矿化,从而提高水中的矿物质含量;当水流经内层时,聚合物层起到去除水中重金属的作用,兼顾了添加矿物质和去除重金属的功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The application discloses a preparation method of a filter core, characterized in that the method comprises the following preparation steps: 1) mineralized particle preparation: mixing a polymer and a mineralized filler according to a mass ratio of 50-500:1, and extruding and granulating by using a melt blending method; 2) polymer mixture preparation: mixing the polymer and a modifier, wherein the mass percentage of the modifier is 5-30%, and the rest is the polymer; and 3) melt-blown filter core preparation. A double-layer filter core with a mineralized layer located at an outer layer and a polymer layer located at an inner layer is prepared by using a layered melt-blown process. The water to be treated flows into the inner layer from the outer layer of the melt-blown filter core. When the water flows through the outer layer, the mineralized filler in the mineralized layer mineralizes the water, thereby improving the mineral content in the water. When the water flows through the inner layer, the polymer layer removes heavy metals in the water, and the functions of adding minerals and removing heavy metals are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a filter element, and more specifically to a method for preparing the filter element. Background Technology

[0002] As people's quality of life continues to improve, their understanding of drinking water is also deepening. The focus has shifted from simply having convenient access to safe drinking water. Correspondingly, water purification technologies are constantly being updated, transitioning from traditional municipal tap water to pure water machines based on reverse osmosis technology.

[0003] However, while reverse osmosis solves the problem of drinking water safety, its removal of beneficial minerals from the water reduces the health benefits of the water produced by a water purifier. To compensate for this shortcoming, mineralization filters were developed. These filters increase the mineral content of the water by releasing minerals into it.

[0004] There are two molding methods for mineralized filter elements: sintering and extrusion molding. Currently, sintering is the most common method for making filter elements from ore. However, sintering has high processing costs, and the large temperature and pressure variations during production make it difficult to balance the structure of the raw materials, resulting in significant raw material losses and low finished product yields. Automated production is also very difficult. Based on the characteristics of raw materials and improvements to existing mineralized product processes, a new extrusion molding process has been developed. This process can significantly improve production efficiency and yield, has a high degree of automation, and greatly reduces costs and losses, making it very suitable for future industrialization needs. Therefore, using extrusion molding to prepare mineralized filter elements is the future development trend.

[0005] For example, Chinese invention patent CN112919850A (application number 202110172345.5), entitled "An Extruded Strontium Mineralized Filter Cartridge and Its Preparation Method," discloses a filter cartridge formula composed of the following materials in different proportions: 20-50 parts activated zeolite powder, 5-30 parts activated strontium ore powder, 10-30 parts activated maifanite powder, 200-300 parts activated carbon powder, and 20-50 parts low molecular weight polyethylene powder. The preparation method of this filter cartridge consists of the following steps: washing natural ore with pure water; crushing and screening the natural ore to obtain ore powder; activating the ore powder to obtain activated zeolite powder, activated strontium ore powder, and activated maifanite powder; mixing the above materials in proportion and extruding them through a carbon rod extruder to obtain the mineralized filter cartridge described in this invention. In this invention, the main function of the mineralization filter cartridge is to stably release minerals into the water. Due to the complex composition of natural minerals, heavy metals are inevitably released during the mineralization of raw water. At the same time, the carbon rod has a weak ability to remove heavy metals, making it difficult to simultaneously remove heavy metals. Summary of the Invention

[0006] The first technical problem to be solved by the present invention is to provide a method for preparing a filter element with mineralization and heavy metal removal functions.

[0007] The second technical problem to be solved by the present invention is to provide a method for cleaning the above-mentioned filter element.

[0008] The technical solution adopted by the present invention to solve the first technical problem is: a method for preparing a filter element, characterized by comprising the following preparation steps: 1) Preparation of mineralized particles: The polymer and mineralized filler are mixed at a mass ratio of 50 to 500:1, and then extruded and granulated by melt blending. 2) Preparation of polymer mixture: Mix the polymer and the modifier, wherein the mass percentage of the modifier is 5-30% and the remainder is polymer; 3) Meltblown filter element preparation: The polymer mixture and mineralized particles are extruded from extruder A and extruder B respectively, and stretched into filaments in hot air at 200~300℃. The filaments are then wound on a receiving rod with the polymer layer in the inner layer and the mineralized layer in the outer layer to obtain the meltblown filter element. 4) Amination modification: The meltblown filter element is placed in a 1~10wt% polyamine solution and heated in a water bath at 60~90℃ for 6~18h to modify the polymer layer by amination.

[0009] The polymers used in steps 1) and 2) are at least one of polyethylene, polypropylene, and polytetrafluoroethylene.

[0010] Since the main components of mineralized filler are calcium carbonate, etc., it not only plays a mineralizing role, but also acts as a toughening agent in the matrix material, which is beneficial to improving the mechanical properties of the filter element. However, too much mineralized filler will affect the flowability of the polymer during granulation and cause structural defects. Therefore, it is necessary to control the mass ratio of polymer to mineralized filler to 50 to 500:1.

[0011] Modifiers can react with polyamines, fixing the amine groups into the polymer layer and giving the filter element a stable ability to remove heavy metals. Modifiers act as a medium for the binding of the polymer layer and the amine groups. If the amount used is too low, there will be insufficient amine groups in the polymer layer after amination, making it unable to effectively remove heavy metals; if the amount used is too high, it will reduce the strength of the material and cause structural defects.

[0012] Preferably, in step 1), the mineralization filler includes a mineralized material and an embedding material surrounding the mineralized material, with a mass ratio of mineralized material to embedding material of 1:1 to 1:10. The mineralized material is selected from at least one of maifanite, secondary quartzite, feldspathic quartz sandstone, and rhodochrosite; the embedding material is selected from at least one of zeolite, calcium carbonate, and magnesium carbonate. During the dissolution process of the embedding material, the mineralized material will gradually be exposed, achieving the purpose of slow-release of minerals.

[0013] Preferably, in step 2), the modifier is selected from at least one of styrene-maleic anhydride copolymer, polypropylene-maleic anhydride copolymer, polypropylene-glycidyl methacrylate copolymer, and polypropylene-styrene-maleic anhydride copolymer.

[0014] Preferably, in step 3), the screw speed of extruder A is 200~400 r / min, the screw speed of extruder B is 400~1200 r / min, and the receiving rod speed is 600~1000 r / min. By controlling the screw speeds of extruders A and B, as well as the receiving rod speed, the thickness of the mineralization layer and polymer layer can be controlled. If the screw speed is too slow, the mineralization layer and polymer layer will be too thin, resulting in insufficient contact time between the water flow and the mineralization layer and polymer layer, leading to insufficient release of minerals and ineffective removal of heavy metals. If the screw speed is too fast, the mineralization layer and polymer layer will be too thick, causing high water flow resistance and affecting the water output efficiency of the water purifier.

[0015] Preferably, in step 3), the spinneret temperature of extruder A and extruder B is 200~300℃, and the extruder temperature is 250~350℃. During the meltblowing process, the material passes through the extruder cavity sequentially, is ejected through the spinneret, and finally cools on the receiving rod to obtain the finished product. For polymers, increasing the temperature can reduce the polymer viscosity. Therefore, the extruder temperature is set relatively high to facilitate polymer flow. When the polymer reaches the spinneret, the set temperature of the spinneret is lowered to facilitate the cooling and molding of the liquid polymer. If both temperatures are too high, the meltblown fibers are too fine, increasing the density of the filter element and increasing water flow resistance; if both temperatures are too low, the meltblown fibers are too coarse, reducing the effective contact area between the water flow and the mineralization layer and polymer layer.

[0016] Preferably, in step 4), the solute in the polyamine solution is at least one of chitosan, N-carboxymethyl chitosan, ethylenediamine, polyethyleneimine, polyallylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyvinylimidazolium, piperazine, p-phenylenediamine, m-phenylenediamine, and polyvinylpyrrolidone, and the solvent is water or a mixture of at least one of methanol, ethanol, and acetone with water.

[0017] Preferably, in step 3), the mineralization layer has a thickness of 6-20 mm, a fiber diameter of 5-20 μm, and a pore size of 5-20 μm; the polymer layer has a thickness of 15-25 mm, a fiber diameter of 5-20 μm, and a pore size of 0.5-10 μm. The mineralization layer releases minerals into the water, so it only needs to be in contact with water; too small a pore size will increase resistance and affect the filter cartridge's throughput. The polymer layer removes heavy metals from the water. Its principle is that the amine groups on its surface adsorb the heavy metals into the water. This process requires a certain distance between the two layers; too large a pore size will reduce the adsorption effect. Similarly, the polymer layer is thicker than the mineralization layer to ensure a longer contact time between the water and the adsorbent material, ensuring sufficient removal of heavy metals.

[0018] The technical solution adopted by the present invention to solve the second technical problem is: a method for cleaning a filter element, characterized in that: bubble water with a pH of 2 to 4 is introduced, and the diameter of the bubbles in the bubble water is 0.1 μm to 10 μm.

[0019] On one hand, bubbles can contact the fibers containing functional groups in the filter element, creating cavitation on their surface and eliminating contaminants, thus achieving cleaning and regeneration. On the other hand, bubbles can penetrate the filter element through the pores on its surface, entering the interior for overall cleaning and regeneration. If the bubble diameter is too large, it cannot enter the inner layer of the filter element; if the bubble diameter is too small, the cleaning effect is poor.

[0020] Furthermore, the acidic water used reacts with and dissolves the encapsulating material in the mineralized functional layer, thus helping to remove adhering contaminants; it also causes the heavy metals originally adsorbed on the polymer layer to leach out. The combined effect of the acidic water and air bubbles allows the contaminated filter cartridge to be reused.

[0021] Preferably, the sparkling water contains at least one of carbonic acid, citric acid, and acetic acid.

[0022] Compared with the prior art, the advantages of the present invention are as follows: a double-layer filter element with a mineralization layer on the outer layer and a polymer layer on the inner layer is prepared by a layered melt-blown process. The water to be treated flows from the outer layer of the melt-blown filter element into the inner layer. When the water flows through the outer layer, the mineralization filler in the mineralization layer mineralizes it, thereby increasing the mineral content in the water. When the water flows through the inner layer, the polymer layer removes heavy metals from the water, thus combining the functions of adding minerals and removing heavy metals. Detailed Implementation

[0023] The present invention will be further described in detail below with reference to the embodiments.

[0024] This invention provides three embodiments and one comparative example.

[0025] The filter element preparation in Example 1 includes the following steps: 1) Preparation of mineralized particles: Polyethylene and mineralized filler are mixed at a mass ratio of 100:1, and extruded and granulated by melt blending. The mineralized filler includes mineralized material and embedding material covering the periphery of the mineralized material, with a mass ratio of mineralized material to embedding material of 1:2; the mineralized material is selected from maifanite, secondary quartzite, and feldspathic quartz sandstone; the embedding material is selected from zeolite and calcium carbonate.

[0026] 2) Preparation of polymer mixture: Polyethylene and styrene-maleic anhydride copolymer are mixed, wherein the mass percentage of the modifier is 25% and the remainder is polyethylene; 3) Meltblown filter element preparation: The polymer mixture and mineralized particles are extruded from extruder A and extruder B respectively, and stretched into filaments in hot air at 250°C. The filaments are then wound onto a receiving rod with the polymer layer on the inner layer and the mineralized layer on the outer layer to obtain the meltblown filter element. The screw speed of extruder A is 350 r / min, the screw speed of extruder B is 1100 r / min, and the receiving rod speed is 800 r / min. The spinneret temperature of extruders A and B is 280°C, and the extruder temperature is 320°C.

[0027] 4) Amination modification: The meltblown filter element is placed in an 8wt% chitosan aqueous solution and heated in a water bath at 80℃ for 16h to modify the polymer layer by amination.

[0028] The filter element preparation in Example 2 includes the following steps: 1) Preparation of mineralized particles: Polyethylene and mineralized filler are mixed at a mass ratio of 300:1, and extruded and granulated by melt blending. The mineralized filler includes mineralized material and embedding material covering the periphery of the mineralized material, with a mass ratio of mineralized material to embedding material of 1:5; the mineralized material is selected from maifanite, secondary quartzite, and feldspathic quartz sandstone; the embedding material is selected from zeolite and calcium carbonate.

[0029] 2) Preparation of polymer mixture: Polyethylene and styrene-maleic anhydride copolymer are mixed, wherein the mass percentage of the modifier is 15% and the remainder is polyethylene; 3) Meltblown filter element preparation: The polymer mixture and mineralized particles are extruded from extruder A and extruder B respectively, and stretched into filaments in hot air at 220°C. The filaments are then wound onto a receiving rod with the polymer layer on the inner layer and the mineralized layer on the outer layer to obtain the meltblown filter element. The screw speed of extruder A is 300 r / min, the screw speed of extruder B is 900 r / min, and the receiving rod speed is 700 r / min. The spinneret temperature of extruders A and B is 250°C, and the extruder temperature is 300°C.

[0030] 4) Amination modification: The meltblown filter element is placed in a 5wt% chitosan aqueous solution and heated in a water bath at 70℃ for 12h to modify the polymer layer by amination.

[0031] The filter element preparation in Example 3 includes the following steps: 1) Preparation of mineralized particles: Polyethylene and mineralized filler are mixed at a mass ratio of 500:1, and extruded and granulated by melt blending. The mineralized filler includes mineralized material and embedding material covering the periphery of the mineralized material, with a mass ratio of mineralized material to embedding material of 1:8; the mineralized material is selected from maifanite, secondary quartzite, and feldspathic quartz sandstone; the embedding material is selected from zeolite and calcium carbonate.

[0032] 2) Preparation of polymer mixture: Polyethylene and styrene-maleic anhydride copolymer are mixed, wherein the mass percentage of the modifier is 10% and the remainder is polyethylene; 3) Meltblown filter element preparation: The polymer mixture and mineralized particles are extruded from extruder A and extruder B respectively, and stretched into filaments in hot air at 280°C. The filaments are then wound onto a receiving rod with the polymer layer on the inner layer and the mineralized layer on the outer layer to obtain the meltblown filter element. The screw speed of extruder A is 200 r / min, the screw speed of extruder B is 500 r / min, and the receiving rod speed is 600 r / min. The spinneret temperature of extruders A and B is 220°C, and the extruder temperature is 250°C.

[0033] 4) Amination modification: The meltblown filter element is placed in a 2wt% chitosan aqueous solution and heated in a water bath at 65℃ for 10h to modify the polymer layer by amination.

[0034] The difference between the comparative example and Example 1 is that the polymer layer is omitted, and the filter element is prepared using only extruder B.

[0035] The dimensions of the obtained embodiments were inspected, and the specific inspection results are shown in Table 1.

[0036] The testing method was as follows: A long strip of thin skin, approximately 5cm in length, 3cm in width, and 1-2mm thick, was cut from the filter element using a blade. The fiber diameter and pore size were then measured under a microscope. Specific test results are shown in Table 1. The obtained examples and comparative examples were subjected to the following performance tests. The test methods are as follows, and the specific test results are shown in Table 2. It can be seen that the examples have more obvious mineralization performance and heavy metal removal performance, especially Example 1, which is the best. The comparative examples have a lower heavy metal removal effect due to the lack of a polymer layer.

[0037] 1) Mineralization properties: The concentrations of the inflow and outflow samples were measured, and then calculated using equation (1): Where: T2 is the effluent sample concentration, and T1 is the inflow sample concentration.

[0038] 2) Heavy metal removal performance: The concentrations of inflow and outflow samples were measured, and then calculated using equation (2): Where: C1 is the inflow sample concentration, and C2 is the outflow sample concentration.

[0039] In Example 1, during the use of the filter cartridge, it was set to flush with water containing bubbles of different diameters at pH 2 every 6 hours, with a flow rate of approximately 2.5 L / min * 60 min * 6 = 750 L. The decline in effluent quality with the flow rate was measured, and the results are shown in Table 3 below. It can be seen that, in terms of flow rate, mineral concentration, and heavy metal removal efficiency, the slowest decline was observed when using bubble sizes of 0.1–10 μm, followed by bubble sizes of 20–50 μm. The most significant decline occurred when no bubbles were used.

[0040] Table 1. Size Detection in Embodiments of the Invention

[0041] Table 2 Performance of the embodiments and comparative examples of the present invention

[0042] Table 3. Relationship between filter cartridge flow rate, product water quality, and micro / nano bubble size during long-term use.

Claims

1. A method for preparing a filter element, characterized in that, The preparation steps include the following: 1) Preparation of mineralized particles: The polymer and mineralized filler are mixed at a mass ratio of 50 to 500:1, and then extruded and granulated by melt blending. 2) Preparation of polymer mixture: Mix the polymer and the modifier, wherein the mass percentage of the modifier is 5-30% and the remainder is polymer; 3) Meltblown filter element preparation: The polymer mixture and mineralized particles are extruded from extruder A and extruder B respectively, and stretched into filaments in hot air at 200~300℃. The filaments are then wound on a receiving rod with the polymer layer in the inner layer and the mineralized layer in the outer layer to obtain the meltblown filter element. 4) Amination modification: The meltblown filter element is placed in a 1~10wt% polyamine solution and heated in a water bath at 60~90℃ for 6~18h to modify the polymer layer with amination. The polymers used in steps 1) and 2) are at least one of polyethylene, polypropylene, and polytetrafluoroethylene.

2. The method for preparing the filter element according to claim 1, characterized in that: In step 1), the mineralization filler includes mineralization material and embedding material covering the outer periphery of the mineralization material, and the mass ratio of mineralization material to embedding material is 1:1 to 1:10; the mineralization material is selected from at least one of maifanite, secondary quartzite, feldspathic quartz sandstone, and rhodochrosite; the embedding material is selected from at least one of zeolite, calcium carbonate, and magnesium carbonate.

3. The method for preparing the filter element according to claim 1, characterized in that: In step 2), the modifier is selected from at least one of styrene-maleic anhydride copolymer, polypropylene-maleic anhydride copolymer, polypropylene-glycidyl methacrylate copolymer, and polypropylene-styrene-maleic anhydride copolymer.

4. The method for preparing the filter element according to claim 1, characterized in that: In step 3), the screw speed of extruder A is 200~400 r / min, the screw speed of extruder B is 400~1200 r / min, and the receiving rod speed is 600~1000 r / min.

5. The method for preparing the filter element according to claim 1, characterized in that: In step 3), the spinneret temperature of extruder A and extruder B is 200~300℃, and the extruder temperature is 250~350℃.

6. The method for preparing the filter element according to claim 1, characterized in that: In step 4), the solute in the polyamine solution is at least one of chitosan, N-carboxymethyl chitosan, ethylenediamine, polyethyleneimine, polyallylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyvinylimidazolium, piperazine, p-phenylenediamine, m-phenylenediamine, and polyvinylpyrrolidone, and the solvent is water or a mixture of at least one of methanol, ethanol, and acetone with water.

7. The method for preparing the filter element according to any one of claims 1 to 6, characterized in that: In step 3), the thickness of the mineralization layer is 6~20mm, the fiber diameter is 5~20μm, and the pore size is 5~20μm; the thickness of the polymer layer is 15~25mm, the fiber diameter is 5~20μm, and the pore size is 0.5~10μm.

8. A method for cleaning a filter element prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Sparkling water with a pH of 2 to 4 is introduced, and the diameter of the bubbles in the sparkling water is 0.1 μm to 10 μm.

9. The method for cleaning the filter element according to claim 8, characterized in that: The sparkling water contains at least one of carbonic acid, citric acid, and acetic acid.

Citation Information

Patent Citations

  • Extrusion molding strontium mineralization filter element and preparation method thereof

    CN112919850A

  • Melt-blown filter element and preparation method thereof

    CN102580401A